Pengembangan Nilai-Nilai Demokratis Mahasiswa Melalui Pendidikan Kewarganegaraan - Adisel Adisel; Suryati Suryati (IJOCE: Indonesia Journal of Civic Education, 2021)
ABSTRACT The purpose of this study was to determine the development of democratic values in students through civic education. This study uses a descriptive method with a qualitative approach. The results of the study show that the democratic values of students through civic education are one of them having tolerance, freedom of expression, respect for differences of opinion, upholding and human dignity. The conclusion of this research is that students who understand civic education will be able to practice democratic values in society. Keywords: Citizenship Education, Democratic Values, Students.